Effects of intercalated water on the lubricity of sliding layers under load: a theoretical investigation on MoS2. (21st June 2021) - Stella, Martina; Lorenz, Christian D; Clelia Righi, Maria
Abstract: Two-dimensional (2D) materials, such as graphene and molybdenum disulfide (MoS2 ) have recently become some of the most studied nano-materials due to their wide array of technological and industrial applications. Among these, they display great potential as solid lubricants. Friction properties of 2D-materials, however, are very sensitive to environmental conditions, e.g. humidity. In MoS2, for instance, humidity can hamper its tribologic performances. Past experiments and recent ab-initio molecular dynamics simulations have highlighted that, at ordinary temperatures, a possible reason for lower lubricity is the physical interaction of water with the layers. It is, therefore, crucial to better understand the microscopic mechanisms underlying this behaviour, in order to optimise the lubrication performance of these materials. In this paper we used density functional theory simulations and classical molecular dynamics simulations to provide a multi-scale description of how external load affects the energetic, structural and dynamic properties of intercalated water between MoS2 layers. As a result of combining these two different approaches, we provide an atomistic description of the role of intercalated water in modifying the frictional behaviour of physically interacting layers, e.g. MoS2 . The identified interlocking mechanism, which is enhanced under load, is relevant for understanding the frictional effects observed for water confined in slit nanopores, and for nanofluidics applications.